Time resolved infrared studies of reactive intermediates - Turner, Jack (2018)
Chapter 1: Introduction This Chapter provides an introduction to the study of reactive intermediates and the specialised techniques which have been developed in order to study these extremely short lived species. In particular, it provides an overview of ultrafast Time Resolved Infrared Spectroscopy (TRIR). This key technique underpins a large amount of the work presented in this Thesis as well as a description of the apparatus and methods used across the other Chapters of this Thesis. Chapter 2: Ultrafast TRIR studies of rhenium complexes of thioether substituted hexaazatrinapthylene ligands The excited states and photophysical properties of mono, bi and trinuclear (Re(CO)3Cl) complexes of the 2,3,8,9,1314-hexa (octyl-thioether)-1,6,7,12,13,18-hexaazatrinapthylene ligand (HATN-S(C8H17)6) have been investigated using ultrafast TRIR spectroscopy. These measurements are supported by theoretical calculations and resonance Raman spectroscopic investigations of these compounds. The position and the intensity of the (CO) bands of the photoexcited species directly report on the electron transfer/distribution in the excited state. In all cases the observed product bands were blue shifted compared to the parent, this is consistent with electron transfer away from the metal centre. The observed shift for the thioether substituted HATN complexes studied here was smaller than that reported for the analogous HATN-Me6 complexes, indicating reduced electron transfer upon excitation. Red shifted product bands corresponding to “spectator” metal centres were also observed for the bi and trinuclear species, these bands were shifted by approximately the same amount as for the HATN-Me6 species, indicating a similar reduction of the HATN core upon excitation. These results are consistent with the formation of a dual charge transfer ILCT/MLCT excited state involving electron donation from both a metal centre and the thioether moieties upon excitation. Chapter 3: Ultrafast TRIR studies of rhenium and platinum complexes of Pyridyl-1,2,3-Triazole and related ligands The excited states and photophysics of a series of substituted rhenium and platinum complexes that contain a 2-pyridyl-1,2-3-triazole ligand, an easily modified analogue of the common 2,2’-bipyridine (bpy)ligand, have been studied by TRIR spectroscopy. The compounds are found to be analogous of similar complexes with bpy, exhibiting MLCT or MLLCT exicted states (in the case of the (Re(CO)3X) and (Pt(CCHPh)2) complexes respectively). Changing the substitution of the triazole ring has little effect on the excited state band positions, this is attributed to the insulating effect of the triazole moiety. Complexes substituted with conjugated phenyl groups on the triazole ring exhibit greatly increased excited state lifetimes than those substituted with non-conjugated benzyl groups. This is attributed to the rigid rotor effect. The addition of an electron donating triphenylamine group to the pyridyl moiety results in the observation of ILCT states. Chapter 4: Towards long lived alkane and noble gas complexes from cationic piano stool complexes in the fluorous phase The synthesis and characterisation of a series of cationic transition metal tricarbonyl half sandwich complexes solubilised in perfluoroalkane solvents by means of the weakly coordinating, fluorous solubilising anion tetrakis(3,5-bis(perfluorohexyl)phenyl)borate (BArF64) is described. These complexes were photolysed in perfluoroalkane solutions doped with methane, heptane and xenon and followed by ultrafast TRIR spectroscopy with the aim of generating long-lived organometallic alkane and noble gas complexes suitable for study by NMR at room temperature. While no organometallic alkane or noble gas complexes were observed, several novel transition metal-BArF64 zwitterionic species are generated upon photolysis. These species are the result of -2 binding of one of the aryl moieties of the BArF64 anion to the vacant coordination sites generated following photoejection of a carbonyl ligand. While highly reactive they are long lived and appear to be permanent photoproducts. In the case of the rhenium complex an additional product band assigned as a dimeric species is also observed. Chapter 5: Towards the synthesis of fluorous phase soluble cationic piano stool complexes. The synthesis of fluorous tagged cationic transition metal tricarbonyl complexes is explored with the eventual aim of performing fluorous phase TRIR experiments utilising the more weakly coordinating (but less solubilising) anion tetrakis(perfluoro-tert-butoxy)aluminate in place of the previously studied BArF64 anion. Several routes to perfluoroalkyl arene ligands are explored and evaluated, as is the use of different lengths of alkyl spacer to insulate the ligand binding site from the strong electron withdrawing effects of the perfluoroalkyl moiety. This process lead to the synthesis of the new complexes [(m-(3-(perfluorooctyl)-propyl)n-benzene)manganesetricarbonyl] hexafluorophosphate for n =1-3. These compounds are soluble in the fluorous phase despite their charge. The use of the m-(3-(perfluorooctyl)-propyl)n-benzene ligand to solubilise complexes of rhenium and rhodium was also attempted. The addition of methyl groups to the ring was explored as a route to additional steric bulk and a more electron rich, strongly binding ligand. In addition to arenes, the fluorous tagging of other ligand systems was also investigated, including cyclopentadienyl and tris(1-pyrazolyl)methane.